PENERAPAN PENILAIAN AUTENTIK ASPEK KOGNITIF PADA PEMBELAJARAN IPS DI SMA N 5 PADANG - Handayani, Febri Kurnia; Anwar, Syafri (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
The performance of students in the learning process may require assessment. One way to conduct such assessment is through authentic assessment. This research aims to analyze the planning and implementation of authentic assessment by Social Studies teachers at SMA N 5 Padang. The research method employed is qualitative research with data collection techniques through interviews, observation, and documentation. The findings reveal that Social Studies teachers have a deep understanding of the concept of authentic assessment and are able to integrate it into their teaching practices. The implementation of authentic assessment is carried out meticulously and carefully by Social Studies teachers through the use of techniques and instruments that align with the learning objectives. Moreover, no significant barriers were found in implementing authentic assessment. The conclusion drawn from this research is that Social Studies teachers at SMA N 5 Padang have been able to plan and implement authentic assessment of cognitive aspects effectively.